Two Digestive Trypsins Occur in Three Species of Neotropical Anophelines - Caroci, A. S.; Calvo, E.; Ribolla, P. E. [UNESP]; De Bianchi, A. G.; Marinotti, O. (My University, 2003)
Trypsin activity increases in the midgut of Anopheles aquasalis, Anopheles albitarsis, and Anopheles darlingi after a bloodmeal. The activity returns to basal levels at the time the blood is completely digested. Affinity chromatography, reversed-phase high performance liquid chromatography (HPLC), and sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) were used to sequentially purify the mosquito trypsins found in the midguts at 24 h after feeding. Amino-terminal sequencing of the purified trypsins showed the occurrence of two distinct trypsins in the midgut of each of the mosquitoes studied. The sequences obtained are similar to those of the trypsins of other hematophagous insects.
Keywords: Anopheles; Malaria vector; Trypsin; trypsin; amino acid sequence; animal; blood; Brazil; chemistry; classification; comparative study; digestion; enzymology; feeding behavior; genetics; human; isolation and purification; kinetics; metabolism; molecular genetics; nucleotide sequence; parasitology; physiology; sensitivity and specificity; sequence alignment; sequence homology; Amino Acid Sequence; Animals; Blood; Conserved Sequence; Digestion; Feeding Behavior; Humans; Kinetics; Molecular Sequence Data; Sensitivity and Specificity; Sequence Alignment; Sequence Homology, Amino Acid; Albitarsis; Animalia; Anopheles albitarsis; Anopheles aquasalis; Anopheles darlingi; Hexapoda